Finite Element Analysis on ballistic impact performance of multi-layered bulletproof vest impacted by 9 mm bullet - Azhari Sastranegara; Kevin Eka Putra; Edmun Halawa; Nanang Ali Sutisna; Ameen Topa (Universitas Mercu Buana, 2023)
Simulation is one of the most effective ways to reduce the cost and time needed to test the quality of a bulletproof vest. The widely applied method to predict the behavior of the materials is a macro-homogeneous model. However, even though it is low in computational cost, it has some accuracy issues. This work presents finite element analysis with both macro-homogeneous and meso-heterogeneous models to predict the behavior of the Kevlar composites during ballistic impact and qualitatively compares the simulation results with the experimental ones. The simulation reliability was ensured by numerical parameters such as the system energy balance and the limitation of artificial energy. The simulation results showed that the meso-heterogeneous yarn model successfully produced more detailed impact damage than the macro-homogenous model. In addition, the deformation of the Kevlar, the bullet, and the steel plate was close to the experiment results. The result was expected to be used as a consideration in determining the model type for another similar research.